Adaptation and validation of the Utrecht Work Engagement Scale (UWES) applied to social workers in Portugal - Teles, Helena (2017)
Objective: The present study aims to evaluate the items, and respective dimensions, of the Utrecht Work Engagement Scale (UWES-17) of Schaufeli e Bakker (2009) when applied to social workers exercising their profession in Portugal (UWES-17). Method: The Portuguese version of the UWES was applied to a sample of 1369 Portuguese social workers, 94% of which female and 6% male, with an average age of 39 years (standard deviation = 8.99). The most frequent academic qualification is graduation (63.8%) and in terms of professional activity they had, in average terms, 12.99 years of experience (standard deviation = 8.28). The reliability of the scale was assessed using the Chronbach alpha coefficient and the validity using the exploratory factorial analysis. Quantitative methodological research was used. Results: The results obtained agree with the values presented in previous studies regarding their internal consistency, both of the 17 items that make up the scale and of its three dimensions ("force", "dedication" and "absorption"). The UWES-17 in this study presents a factorial structure of three factors, just like the original study, but the constitution of the items of each dimension is different. The UWES-17 scale presents good psychometric characteristics and good internal consistency. Conclusions: The UWES-17 scale presents good psychometric characteristics and good internal consistency.